USE OF CARTON MEDIA TO INCREASE STUDENT LEARNING RESULT IN LEARNING MATHEMATICS OF MATERIALS TO BUILD CUBE ROOMS AND BEAMS IN PRIMARY SCHOOL - Teti Rohmawati; Eni Supriati; Rizki Pebriana (COLLASE (Creative of Learning Students Elementary Education), 2018)
This study is based on student learning activities when learning takes place only a few students who pay attention. The results of the mathematics exercise and repetition of students also always get a low score. The use of carton media can help students understand abstract mathematical concepts and can make students more activities in the learning process. This method of classroom action research takes the form of a cycle that will last more than one cycle depending on the success of the target to be achieved. The use of carton media can improve student learning outcomes, either individually or in groups. This is evident from the results of student learning initial data percentage of 35.71%. However, after applying the use of carton media students' learning outcomes increased by 71.42% and in the second cycle reached 92.85%. In addition, the value of the group also increased, the first cycle was 85.71%, and in cycle II reached 100%